A rede social corporativa nos processos e nos modelos de negócios: um estudo sobre seus impactos - Almeida, Rosana de (2017)
Gradually, increasingly seek to improve the relationship with its external customers and internal, increase productivity and collaboration. With the rise of Web 2.0, the use of social technologies, especially social networks, has favored the knowledge exchange, agility in communication, the informations sharing and resources, the process internal and external and customers approchement. Considering these aspects, this study aims to identify the impact of Corporate Social Network in process and business models on an organization. The corporate social networks can promote the internal processes, especially the business processes and, from change in these processes with Social Network can deliver the emergence of new business models, thus creating value for the organization. This study contributes by presenting a new approach on Corporate Social Network, in relation to the processes and business models. It provides subsidies for the implantation projects and use of Social Net Corportiva of organizations, advances in the concepts of its use as social software and attainment of results for the managers. Presented the aspects on the use and the benefits of the use of the Technology of Information; the Social Nets and the Corporative Social Nets, its infrastructure, environment and functionalities. One identifies the types of business processes and argue aspects of the Social BPM - Business Process Management, beyond the business-oriented Models that conceptualized and characterized. The change and its importance in the enterprise environment and the creation of value for the organization from the processes and of the models of business also are treated. Research based on the qualitative approach. This is a case of study of a Brazilian business group, based in the state of Minas Gerais. The data constructed by means of the technique of semistructuralized interview. In the analysis of the empirical phase the content analysis technique was used to examine the data, supported by qualitative data analysis software. It verified in 568 references that the Corporative Social Net (CSN) could be use as social software in the business processes and, still, it can enable the emergence of new MN from its use. The creation of value by CSR is evidenced in the internal processes of the commercial area, generating value to the organization. The results showed that the implementation and use of CSR in business processes impact the business group here studied. The agility, the co-creation in the processes, creates value and positive results for the organization.